2020
DOI: 10.1097/bpb.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

Operative treatment of chronic ulnar collateral ligament humeral origin avulsion fracture in young baseball players

Abstract: Chronic ulnar collateral ligament humeral origin avulsion fracture in young baseball players is a rare condition and a difficult problem to treat. Eight high school or college student baseball players with onset of symptoms in their adolescent ages were collected in this series. Their mean age at surgical intervention was 17.8 ± 1.99 years. The fracture was operated on with muscle splitting, ulnar nerve-sparing technique. Suture anchors were employed to fix the avulsed fragment. Visual analog scale, Mayo elbow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Su et al reported eight cases of chronic ulnar collateral ligament humeral origin avulsion fracture in young baseball players. 8 In that report, no ulnar collateral ligament shortening was encountered and the avulsed fragment could be repositioned in all cases. In addition, there were no cases of ligament shortening in previous reports of chronic avulsion fracture of the anterior cruciate ligament of the knee in adolescents.…”
Section: Discussionmentioning
confidence: 80%
“…Su et al reported eight cases of chronic ulnar collateral ligament humeral origin avulsion fracture in young baseball players. 8 In that report, no ulnar collateral ligament shortening was encountered and the avulsed fragment could be repositioned in all cases. In addition, there were no cases of ligament shortening in previous reports of chronic avulsion fracture of the anterior cruciate ligament of the knee in adolescents.…”
Section: Discussionmentioning
confidence: 80%